2016
DOI: 10.3892/ol.2016.4523
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma educates mesenchymal stromal cells towards vasculogenic mimicry

Abstract: ������������ �������� �������� ���� �����-������������ �������� �������� ���� �����-��y��� ��ro��� ����� (MSC�) �r� r��r����� �o ��� ���or, ��� pro�o�� ���or �����op���� ��� �row��. T�� pr����� ����y w�� p�rfor��� �o ����������� ��� �o���������o� b��w��� ���r������ �����o�� ��� MSC� �� ������o����� �����ry (VM). Nor��� ����� MSC� p����� o� M��r���� w�r� ���b�� �o for� ��p����ry-��k� ��r����r�� (CLS�). By �o��r���, MSC� �o-�����r�� w��� ���r������ �����o�� ���� �����, �����y, Mel Cher, Mel Kor and Mel P, genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In melanoma, the role of ADSC is also debated. Indeed, after co‐culture with melanoma cells, ADSC form capillary‐like structures (Vartanian et al., ), which could support increased tumor vascularization observed in obese melanoma patients. Using mesenchymal stem cells derived from bone marrow, an adipocyte‐rich environment, Sun et al.…”
Section: Role Of Adipose Tissue In Melanoma Progressionmentioning
confidence: 94%
“…In melanoma, the role of ADSC is also debated. Indeed, after co‐culture with melanoma cells, ADSC form capillary‐like structures (Vartanian et al., ), which could support increased tumor vascularization observed in obese melanoma patients. Using mesenchymal stem cells derived from bone marrow, an adipocyte‐rich environment, Sun et al.…”
Section: Role Of Adipose Tissue In Melanoma Progressionmentioning
confidence: 94%
“…Considering the CSCs model, it has been also hypothesized that a fraction of CSCs could differentiate in cells with VM phenotype. Vartanian et al have demonstrated that melanoma cells were able to increase the vasculogenic potential of MSCs by VM. In fact, MSCs derived from adipose tissues of C57BL/6 mice in cocultured with melanoma cells formed vascular‐like network on Matrigel.…”
Section: Tumor Angiogenesis and Cscsmentioning
confidence: 99%
“…Moreover, aggressive melanoma cells but not poorly aggressive melanoma cells induce VM in normal human mesenchymal stromal cells in co-culture. This effect is mediated by VEGFA [ 79 ]. Treatment against aggressive melanoma cells may ignore changes in ECM, decreasing the effectiveness of the therapy.…”
Section: Vasculogenic Mimicry and Tumor Microenvironmentmentioning
confidence: 99%